Complementary and integrative therapies in the scope of nursing: legal aspects and academic-assistance panorama - Cissa Azevedo; Caroline de Castro Moura; Hérica Pinheiro Corrêa; Luciana Regina Ferreira da Mata; Érika de Cássia Lopes Chaves; Tânia Couto Machado Chianca (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: to carry out a documentary study on the legal aspects that support the nurses' performance in the Integrative and Complementary Practices (PIC) and to discuss the panorama of teaching, research, extension and nursing activities in front of PICs. Method: documentary study, whose units of analysis were normative, guidelines, recommendations and clarification notes (n = 17). The data were organized into two categories: "Legal aspects of nurses' performance in ICP and acupuncture" and "Overview of the use of ICPs by nursing in the areas of teaching, research, extension and assistance activities". Results: nurses stand out in the implementation of PIC since the principles of training are congruent to the paradigms of this science, besides having legal support for acting in public and private services in Brazil. There is an incipient movement of nurses working in research and extension in universities, which contributes to the diffusion of knowledge and application of therapies in the community. Conclusion: the institutionalization of PICs in the Unified Health System has increased access and contributed to the provision of comprehensive and multidisciplinary health services. Implications for practice: with ICPs, nurses have achieved autonomy and the possibility of expanding their performance, aiming at a better quality of care.